2016
DOI: 10.1038/nphys3891
|View full text |Cite
|
Sign up to set email alerts
|

Optical manipulation of valley pseudospin

Abstract: The coherent manipulation of spin and pseudospin underlies existing and emerging quantum technologies, including quantum communication and quantum computation 1,2 . Valley polarization, associated with the occupancy of degenerate, but quantum mechanically distinct valleys in momentum space, closely resembles spin polarization and has been proposed as a pseudospin carrier for the future quantum electronics 3,4 . Valley exciton polarization has been created in the transition metal dichalcogenide monolayers using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(234 citation statements)
references
References 39 publications
7
227
0
Order By: Relevance
“…Generation of valley coherence is achieved optically by linearly polarized excitation σ X , which results in strongly linearly polarized neutral exciton (X 0 ) emission [26]. Recent experiments have shown that this valley polarization can be rotated in ML WSe 2 and WS 2 [49][50][51], a first important step towards full control of valley states [87]. The MoS 2 ML is excited by a linearly polarized (σ X ) continuous wave He-Ne laser (1.96 eV) to generate valley coherence (i.e., optical alignment of excitons [80]).…”
Section: Rotation Of Valley Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Generation of valley coherence is achieved optically by linearly polarized excitation σ X , which results in strongly linearly polarized neutral exciton (X 0 ) emission [26]. Recent experiments have shown that this valley polarization can be rotated in ML WSe 2 and WS 2 [49][50][51], a first important step towards full control of valley states [87]. The MoS 2 ML is excited by a linearly polarized (σ X ) continuous wave He-Ne laser (1.96 eV) to generate valley coherence (i.e., optical alignment of excitons [80]).…”
Section: Rotation Of Valley Coherencementioning
confidence: 99%
“…Here, we discuss the possible impact of doping (i.e., contributions from charged excitons) and the dielectric environment. We also show the generation and rotation of robust valley coherence, a coherent superposition of valley states using the chiral optical selection rules [26], an important step towards full optical control of valley states in these 2D materials [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Yet another control route is provided by the Berry phase that underpins the tuning of topological conducting channels 7,8,21 . The same physics is essential for optical control of the valley degree of freedom in quantum materials with hexagonal lattices 22 , including graphene and transition metal dichalcogenides (TMDs). Likewise, the chirality of both electronic and photonic 23,24 effects in quantum materials can be manipulated: chiral currents and propagating chiral hybrid light-matter modes known as polaritons can benefit from topological protection against backscattering [25][26][27] .…”
Section: Nature Materials Doi: 101038/nmat5017mentioning
confidence: 99%
“…Such information can be decisive in the correct determination of transport properties [8,9] or energy relaxation [10][11][12]. A momentum-resolved view of scattering processes will in addition be of uttermost importance in conceiving novel quantum technologies harnessing spin and valley degrees of freedom [13][14][15], as they utilize carrier populations at specific positions in momentum space. While time-and angle-resolved photoemission spectroscopy provides this level of detail for electron dynamics, see, for instance, Refs.…”
mentioning
confidence: 99%